GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 354804 species occurrences available in GBIF matching the query: Country: Costa Rica Geometry: POLYGON((-84.869384 10.366256,-84.869384 9.909332,-84.627685 9.909332,-84.627685 10.366256,-84.869384 10.366256)). The dataset includes 354804 records from 161 constituent datasets: 1 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 888 records from Mollusca of Costa Rica (INBio). 24 records from Phanerogamic Botanical Collections (S). 135 records from MVZ Herp Collection (Arctos). 25 records from University of Vienna, Institute for Botany - Herbarium WU. 2 records from Colección de Entomología - Diptera - Ceratopogonidae. 12 records from MVZ Mammal Collection (Arctos). 483 records from Nematoda of Costa Rica (INBio). 3496 records from LACM Entomology Collection. 150 records from Bee Biology and Systematics Laboratory. 8 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 21999 records from AntWeb. 7 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 362 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from TCWC Marine Invertebrates. 5 records from KUBI Ornithology Tissue Collection. 32 records from Fishbase. 735 records from KUBI Mammalogy Collection. 28 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 1 records from ICN - Herbário do Instituto de Ciências Naturais. 8 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 10 records from Herbario Universidad de Antioquia (HUA). 568 records from Lyman Entomological Museum (LEMQ). 29 records from DMNS Bird Collection (Arctos). 16333 records from Plantae of Costa Rica (INBio). 6 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 138278 records from Insecta of Costa Rica (INBio). 2 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 1 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 136 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 44 records from Myriapoda of Costa Rica (INBio). 6 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 738 records from Museum of Comparative Zoology, Harvard University. 19 records from Australia's Virtual Herbarium. 123560 records from EOD - eBird Observation Dataset. 249 records from iNaturalist Research-grade Observations. 1 records from Global caridean shrimp fauna. 13 records from CONN. 1 records from Onychophora of Costa Rica (INBio). 4 records from mel. 6 records from Estonian University of Life Sciences. 8 records from Essig Museum of Entomology. 21 records from CAS Ichthyology (ICH). 557 records from NMNH occurrence DwC-A. 10 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from NRM-Herpetology. 24 records from Illinois Natural History Survey Insect Collection. 114 records from naturgucker. 410 records from UMMZ Mammal Collection. 9 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 12 records from Registros biológicos del género Piper en el herbario HUA. 1 records from Royal Ontario Museum - Entomology (ROME). 22 records from CM Herps Collection. 311 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 1 records from Lichen herbarium, Oslo (O). 1608 records from LACM Vertebrate Collection. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 2 records from TRTE Herbarium (TRTE). 20534 records from Tropicos Specimen Data. 52 records from Natural History Museum (London) Collection Specimens. 1 records from Natural History Museum, Vienna - Herbarium W. 260 records from Macaulay Library Audio and Video Collection. 1 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 1 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Harold W. Manter Laboratory of Parasitology Collection. 5 records from RBINS collections. 245 records from Field Museum of Natural History (Botany) Fungi Collection. 6 records from Australian National Herbarium (CANB). 6 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 65 records from UWBM Ornithology Collection. 55 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 3 records from The AAU Herbarium Database. 69 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 2 records from Michigan State University Herbarium Lichens. 78 records from LSUMZ Mammals Collection. 8157 records from herbario. 118 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 3 records from SDNHM Birds Collection. 16 records from Arizona State University Amphibian and Reptile Collection. 66 records from Arizona State University Lichen Collection. 20 records from CNMA/Colección Nacional de mamíferos. 42 records from MEXU/Plantas Vasculares. 8 records from MEXU/Tipos de plantas vasculares. 1 records from MEXU/Colección de Briofitas. 21 records from Mammal specimens. 3 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 1 records from Invertebrate Zoology Division, Yale Peabody Museum. 23 records from TTU Mammals Collection. 69 records from Lichen Herbarium Berlin. 5 records from United States National Plant Germplasm System Collection. 7 records from The System-wide Information Network for Genetic Resources (SINGER). 1 records from USU-UTC Specimen Database. 224 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 102 records from invertebratezoology. 1 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1 records from Harvard University Herbaria. 2 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 349 records from MAL. 602 records from Mosquito Occurrence Dataset. 8 records from Programa de repatriación de datos de ejemplares mexicanos. 3 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 6 records from CNIN/Coleoptera. 13 records from University of Alberta Entomology Collection (UASM). 48 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 2 records from WFVZ Bird Collections. 1 records from USF Herbarium. 3 records from Natural History Museum, University of Tartu. 3 records from MLZ Bird Collection (Arctos). 748 records from Field Museum of Natural History (Botany) Seed Plant Collection. 13 records from UA Herbarium. 37 records from Therevid PEET Project. 296 records from Texas A&M University Insect Collection. 61 records from Entomology Division, Yale Peabody Museum. 38 records from Collection Herpetology SMF. 18 records from Collection Crustacea SMF. 5 records from SINGER Coordinator. 2 records from MEXU/Leguminosae. 2 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 1 records from University of Florida Invertebrate Paleontology. 15 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 65 records from Bird Specimens. 38 records from UPCB - Herbário do Departamento de Botânica. 9 records from Queensland Museum provider for OZCAM. 6877 records from Snow Entomological Museum Collection. 113 records from Geographically tagged INSDC sequences. 1 records from Ouellet-Robert entomological collection (QMOR). 70 records from Arácnidos de Centroamérica. 18 records from MSB Mammal Collection (Arctos). 1 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Bernice P. Bishop Museum. 25 records from UMMZ Birds Collection. 14 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 8 records from Botany (UPS). 32 records from Mammalogy Collection - Royal Ontario Museum. 2 records from JPB - Herbário Lauro Pires Xavier. 2 records from Insect Occurrence Data from MIZA. 15 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 4 records from CAS Herpetology (HERP). 72 records from Arachnida of Costa Rica (INBio). 1 records from Revisionary studies on the attine ant genus Trachymyrmex Forel. Part 3: The Jamaicensis group (Hymenoptera: Formicidae).. 114 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 10 records from Global compendium of Aedes aegypti occurrence. 3 records from NCSM Herpetology Collection. 1 records from UB - Herbário da Universidade de Brasília. 374 records from KUBI Herpetology Collection. 4 records from Australian Museum provider for OZCAM. 2 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 28 records from MVZ Bird Collection (Arctos). 9 records from Orchid Herbarium Collection. 15 records from KUBI Ornithology Collection. 602 records from Fungi of Costa Rica (INBio). 13 records from UF FLMNH Ichthyology. 11 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 92 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 16 records from Geneva Herbarium – General Collection (G). 3 records from A new Costa Rican species of Leptanilloides (Hymenoptera: Formicidae: doryline section: Leptanilloidinae).. 5 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 146 records from CAS Botany (BOT). 2 records from Lichen herbarium, UiB. 3 records from HRCB - Herbário Rioclarense.
Keywords: GBIF; biodiversity; species occurrences